Efeito do condicionamento ácido e do envelhecimento na resistência da união adesiva de um adesivo universal ao esmalte dental - Vincenzi, Bárbara (2018)
Purpose: To evaluate the performance of an universal restorative adhesive system (total- and self-etching mode) on bond strength (BS) to the enamel immediately and after 12 months. Materials and methods: Eleven human third molars were sectioned in half to obtain twenty-two samples. The proximal enamel surfaces were planned, polished and randomly divided into 2 groups according to the treatment, and these subdivided (2 groups) according to the storage time, making 4 groups (n = 11): CAI (Scotchbond Universal adhesive-SBU, with prior 37% phosphoric acid conditioning for 15 sec, analyzed immediately); CA12m (same treatment as CAI, analyzed after 12 months aging); SAI group (SBU without prior acid conditioning, analyzed immediately); SA12m (same treatment as SAI, analyzed after 12 months aging). All samples were restored with Scothbond Universal adhesive (SBU) and Filtek Z100 composite resin according to the manufacturer's instructions. The composite resin blocks were built up incrementally. The specimens were stored in deionized for 24 hours and sectioned in sticks (1.0 ± 0.2 mm area) and subjected to microtensile on test machine on 0.5mm/min immediately (24h) and after 12 months . Data were submitted to ANOVA two criteria (p <0.01) followed by the Tukey post-test (p<0.05). Results: Enamel acid etching promoted a significant increase in RU values after immediate traction. However, after 12 months, RU values decreased significantly, with no statistical difference between the groups with and without acid conditioning. Conclusions: Enamel conditioning increased the immediate bond strength of the universal adhesive, and aging after 12 months reduced it.